PENGARUH LATIHAN FISIK I DAN II TERHADAP KEMAMPUAN MENGONTROL PERILAKU KEKERASAN PADA PASIEN PERILAKU KEKERASAN DI RUANG RAWAT INAP RUMAH SAKIT JIWA MUTIARA SUKMA - Ni Made Sumartyawati (Jurnal PRIMA, 2019)
Violent behavior is a response of stressor faced by someone by sowing particular actual violent behaviour to either himself, other people or environment in either verbal or non verbal means to physically or psychologically injure others. The therapy may help such patients is physical exercise I and II. This research is aimed at determining the effect of physical exercise I and II on the ability to control violent behaviour. The research is using method of Pre-Experimental study designed with post-test study with one group pre-test and post-test. This research involved 30 respondents with violent behavior treated in Inpatient room of Mutiara Sukma Mental Hospital, selected through purposive sampling. The data were collected through observation and interview. The data then were statistically examined using Wilcoxon Signed Rank Test within α= 0.05. The research showed that before of relaxation therapy the ability to control violent behaviour, 20 respondents (67%) of them were categorized as poor (unable to control), 10 respondents (33%) were fair (simply able enough to control. This is percentage showed that they are categorized as unable to control the violent behaviour. After they were provided with phisical exercise I and II, 27 of the respondents (90%) were categorized as good or able to fully control violent bihaviour, this is due to the interest of the respondents to follow the physical exercise therapy I and II. It is inferred that physical exercise therapy I and II had significant effect in controlling the violent behaviour. It is suggested that nurses providing the therapy work in appropriate procedure within to reach the fulfilment of the available indicators.